Encarta world English dictionary (Bloomsbury, 1999)
An illustrated dictionary with quick definitions that give instant access to core meanings. Complex technical terms are defined in straightforward English and there is advice on how to avoid mistakes. It also includes an easy-to-use pronunciation system and thousands of geographical and biographical entries.